Field-induced canting of magnetic moments in GdCo5 at finite temperature: first-principles calculations and high-field measurements. (16th July 2018) - Patrick, Christopher E; Kumar, Santosh; Götze, Kathrin; Pearce, Matthew J; Singleton, John; Rowlands, George; Balakrishnan, Geetha; Lees, Martin R; Goddard, Paul A; Staunton, Julie B
Abstract: We present calculations and experimental measurements of the temperature-dependent magnetization of a single crystal of GdCo5 in magnetic fields of order 60 T. At zero temperature the calculations, based on density-functional theory in the disordered-local-moment picture, predict a field-induced transition from an antiferromagnetic to a canted alignment of Gd and Co moments at 46.1 T. At higher temperatures the calculations find this critical field to increase along with the zero-field magnetization. The experimental measurements observe this transition to occur between 44–48 T at 1.4 K. Up to temperatures of at least 100 K, the experiments continue to observe the transition; however, at variance with the calculations, no strong temperature dependence of the critical field is apparent. We assign this difference to the inaccurate description of the zero-field magnetization of the calculations at low temperatures, due to the use of classical statistical mechanics. Correcting for this effect, we recover a consistent description of the high-field magnetization of GdCo5 from theory and experiment.